Co-administration of paclitaxel and 2-methoxyestradiol using folate-conjugated human serum albumin nanoparticles for improving drug resistance and antitumor efficacy. (2nd January 2021) - Liu, Xinyang; Zhao, Taoqian; Xu, Yue; Huo, Pengchao; Xu, Xia; Zhang, Zhenzhong; Tian, Qingfeng; Zhang, Nan
Abstract: The use of chemotherapeutic drug paclitaxel (PTX) for the treatment of tumors has several limitations, including multidrug resistance (MDR) and serious adverse reactions. This research aims to co-encapsulate PTX and the chemosensitizer 2-methoxyestradiol (2-ME) into folate-conjugated human serum albumin nanoparticles (FA-HSANPs) to reduce multiple drug resistance and improve antitumor efficiency. The results show PTX/2-ME@FA-HSANPs had uniform particle size (180 ± 12.31 nm) and high encapsulation efficacy. It also exhibited highly potent cytotoxicity and apoptosis-inducing activities in the G2/M phase of PTX-resistant EC109/Taxol cells. Moreover, PTX/2-ME@FA-HSANPs not only displayed better inhibition of tumor growth in S-180 tumor-bearing mice than PTX alone but also reduced pathological damage to normal tissues. In summary, PTX/2-ME@FA-HSANPs could be a promising vehicle for tumor therapy and reducing drug resistance. This research will also provide references for other MDR treatment. Graphical Abstract: